2021
DOI: 10.1073/pnas.2017537118
|View full text |Cite
|
Sign up to set email alerts
|

Interventions can shift the thermal optimum for parasitic disease transmission

Abstract: Temperature constrains the transmission of many pathogens. Interventions that target temperature-sensitive life stages, such as vector control measures that kill intermediate hosts, could shift the thermal optimum of transmission, thereby altering seasonal disease dynamics and rendering interventions less effective at certain times of the year and with global climate change. To test these hypotheses, we integrated an epidemiological model of schistosomiasis with empirically determined temperature-dependent tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 51 publications
1
51
2
Order By: Relevance
“…We have so far considered how pathogens themselves are able to shape the thermal performance of the host and discussed how an understanding of the thermal ecology of individual host and pathogens, and even populations distributed across geographic regions, may be required to accurately predict, and control, the spread of infectious disease (see also Cator et al, 2020; Sternberg & Thomas, 2014). A recent study by Nguyen et al (2021), however, provides the first evidence that measures implemented to control the spread of pathogens can themselves shape the thermal optima and thermal limits of host and pathogen populations. By simulating the consequences of controlling the vector, a freshwater snail, of the human pathogen underlying schistosomiasis, they show how removal of snails from a population could potentially shift the thermal optimum for disease transmission upwards by nearly 2°C (Nguyen et al, 2021).…”
Section: Thermal Optima and Thermal Limits Are Likely Sensitive To Human Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have so far considered how pathogens themselves are able to shape the thermal performance of the host and discussed how an understanding of the thermal ecology of individual host and pathogens, and even populations distributed across geographic regions, may be required to accurately predict, and control, the spread of infectious disease (see also Cator et al, 2020; Sternberg & Thomas, 2014). A recent study by Nguyen et al (2021), however, provides the first evidence that measures implemented to control the spread of pathogens can themselves shape the thermal optima and thermal limits of host and pathogen populations. By simulating the consequences of controlling the vector, a freshwater snail, of the human pathogen underlying schistosomiasis, they show how removal of snails from a population could potentially shift the thermal optimum for disease transmission upwards by nearly 2°C (Nguyen et al, 2021).…”
Section: Thermal Optima and Thermal Limits Are Likely Sensitive To Human Interventionsmentioning
confidence: 99%
“…A recent study by Nguyen et al (2021), however, provides the first evidence that measures implemented to control the spread of pathogens can themselves shape the thermal optima and thermal limits of host and pathogen populations. By simulating the consequences of controlling the vector, a freshwater snail, of the human pathogen underlying schistosomiasis, they show how removal of snails from a population could potentially shift the thermal optimum for disease transmission upwards by nearly 2°C (Nguyen et al, 2021). This occurs because the additional vector mortality induced by artificial snail removal reduces the relative contribution of natural temperature‐driven mortality, and so allows for an increase in the temperature at which transmission risk will likely peak.…”
Section: Thermal Optima and Thermal Limits Are Likely Sensitive To Human Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, in research on the effects of anti-parasite treatments, models and field experiments have shown that treatment effects on individual hosts do not necessarily lead to equivalent effects in host populations (Fenton, 2013;Nguyen et al, 2021;Pedersen and Antonovics, 2013). The process of parasite transmission among hosts can potentially decouple population dynamics of hosts and parasites from dynamics within host individuals, particularly if the traits that shape the transmission process are temperature dependent (e.g., temperature-dependent activity rate; Casey, 1976).…”
Section: Overview Of Thermal Optima and Parasitismmentioning
confidence: 99%